Educação ambiental como patrimônio: vivências e práticas transformadoras em comunidades da Quarta Colônia - RS - Berger, Eliane Terezinha dos Santos (2023)
This dissertation, which has as its theme “Environmental Education as Heritage: experience and transformative practices in communities of the Fourth Colony-RS”, is linked to the concentration area Architecture and Cultural Heritage and research line Preservation and Material Heritage of the Professional Master in Cultural Heritage. Environmental Education is an important tool to raise awareness for sustainability and preservation of the environment in which we live. The region of the Fourth Colony stands out for its natural and cultural beauties and these must be known and preserved. In view of this, the promotion of Environmental and Heritage Education in schools becomes relevant and necessary to form active citizens who are aware of their responsibilities as citizens. With the curricular component of Heritage Education in the municipality of Restinga Sêca, RS, schools began to adhere to pedagogical strategies that would suit the new demand foreseen in the municipality. For this, it was developed with the students of the Municipal School of Early Childhood Education and Elementary School Dezidério Fuzer located in São Miguel, interior of Restinga Sêca, pedagogical interventions contemplating the importance of knowing, valuing and preserving the natural landscapes in this municipality, and also in neighboring municipalities, considering the relevance of the Geopark UNESCO Quarta Colônia for this region. Soon, tours were carried out in the tourist spots of Restinga Sêca and some regions of the Fourth Colony, in these tours observations and photographic records were made for a later rereading through drawings. At school, toys were made from recyclable materials, lectures with themes related to Heritage and Environmental Education, production of a book with stories about the environment. During the development of the work it was realized that many of the residents of the interior still do not have basic information on how to proceed with the solid household waste generated in their homes. With this, the relevance of a calendar with the dates of dry garbage collection and basic information on the correct disposal of solid household waste, emphasizing recycling as a form of sustainability.